The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0257745
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic performance of rocket (Eruca sativa. Mill.) grown under different regimes of light intensity, quality, and photoperiod

Abstract: In recent years, much effort has been devoted to understanding the response of plants to various light sources, largely due to advances in industry light-emitting diodes (LEDs). In this study, the effect of different light modes on rocket (Eruca sativa. Mill.) photosynthetic performance and other physiological traits was evaluated using an orthogonal design based on a combination between light intensity, quality, and photoperiod factors. Some morphological and biochemical parameters and photosynthetic efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
3
19
1
Order By: Relevance
“…Plants exposed to a mixture of red and blue light had greater photoreceptor excitation, like phytochromes, cryptochromes, and phototropins, and had higher photosynthetic activity than plants exposed to monochromatic red or blue light 46 . According to Yousef and coauthors showed that a combination of R and B LED light with a high R portion was effective in producing vigorous grafted tomato seedlings compared to blue and red light alone 20 , 47 , 48 . Also, Dong et al 49 , as compared to blue light alone, red light alone, and sunshine, combined red and blue light (1/3 blue light at 450–460 nm + 2/3 red light at 620–630 nm, at 400 lx and 12 h photoperiod for 60 days) improved the DW and bio efficiency of Cordyceps militaris mushroom.…”
Section: Discussionmentioning
confidence: 99%
“…Plants exposed to a mixture of red and blue light had greater photoreceptor excitation, like phytochromes, cryptochromes, and phototropins, and had higher photosynthetic activity than plants exposed to monochromatic red or blue light 46 . According to Yousef and coauthors showed that a combination of R and B LED light with a high R portion was effective in producing vigorous grafted tomato seedlings compared to blue and red light alone 20 , 47 , 48 . Also, Dong et al 49 , as compared to blue light alone, red light alone, and sunshine, combined red and blue light (1/3 blue light at 450–460 nm + 2/3 red light at 620–630 nm, at 400 lx and 12 h photoperiod for 60 days) improved the DW and bio efficiency of Cordyceps militaris mushroom.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal spectral distribution range promotes plant growth with optimum life span and light energy efficiency 13 . Many studies investigated LED effects on growth, development, morphology, and photosynthesis in different plants 14 18 , used a combination of fluorescent and LED sources 19 , replaced fluorescent light tubes with LEDs 20 , or utilized various LED combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, citrus fruits are categorized into the sugar accumulation type [16]. The photosynthetic products produced by the leaves are converted into starch in the early stage of fruit development [12,17,18]. In the later stage of fruit development, the accumulated starch is converted into soluble sugars, which causes a sharp increase in sugar content [6].…”
Section: Introductionmentioning
confidence: 99%